Supplementation of sperm cryopreservation media with H2S donors enhances sperm quality, reduces oxidative stress, and improves in vitro fertilization outcomes - Asefeh Mohammadi; Farnoosh Jafarpour; Nima Tanhaei Vash; Mehdi Hajian; Mohammad Hossein Nasr-Esfahani (Scientific Reports, 2024)
Abstract Cryopreservation of sperm can cause oxidative stress and damage, leading to decreased different functional parameters and fertilization potential. In this study, we evaluated two types of H2S donors: NaHS, a fast-releasing donor, and GYY4137, a slow-releasing donor during cryopreservation of goat sperm. Initially, we determined that 1.5 and 3 μM NaHS, and 15 and 30 μM GYY4137 are optimal concentrations that improved different sperm functional parameters including motility, viability, membrane integrity, lipid peroxidation, and ROS production during incubation at 38.5 °C for 90 min. We subsequently evaluated the impact of the optimal concentration of NaHS and GYY4137 supplementation on various functional parameters following thawing during cryopreservation. Our data revealed that supplementation of extender improved different parameters including post-thaw sperm motility, viability, membrane integrity, and reduced DNA damage compared to the frozen-thawed control group. The supplementation also restored the redox state, decreased lipid peroxidation, and improved mitochondrial membrane potential in the thawed sperm. Finally, we found that supplementation of the extender with NaHS and GYY4137 enhanced IVF outcomes in terms of blastocyst rate and quality of blastocysts. Our results suggest that both donors can be applied for cryopreservation as antioxidants to improve sperm quality and IVF outcomes of frozen-thawed goat sperm.